Retroalimentación desde el relato docente en contexto intercultural en situación de pandemia: Feedback from the Teaching Report in an Intercultural Context in a Pandemic Situation - Fuentes-Henríquez, Carolina; Mansilla Sepúlveda, Juan (Universidad del Zulia, 2021)
This manuscript analyzes the concept of academic feedback and how this process is carried out in the context of online education and pandemic from an intercultural perspective. It presents an analysis from the perspective of the trainers of trainers where the experience of the teacher and the reality of the students and the gaps that distance education has evidenced from the formative evaluation and its potential in the educational field are shown. It is concluded that the conception of feedback is still very conservative, with few indications related to classical maieutics. This is a qualitative research of the article type.